Transformation of Land Registration Through Electronic Certificates to Overcome Overlapping Certificates in Indonesia - Kevin Veronica Halim; Ariawan Gunadi (Journal of Law, Politic and Humanities, 2024)
Land is a crucial natural resource for human life, serving as a residence, a basis for economic activities, and a symbol of status. Effective land registration is vital for providing legal certainty and preventing disputes, particularly regarding the issue of overlapping certificates. This writing will discuss the role of electronic certificates as a solution to address this issue, considering that the increasing number of registered land parcels can trigger ownership conflicts. Although the existing legal framework provides a clear structure, challenges such as a lack of accurate data, complex bureaucracy, and high registration costs still hinder implementation. Electronic certificates are expected to enhance transparency and efficiency in land rights management; however, they do not guarantee the elimination of future disputes. Therefore, community education and improved oversight among relevant agencies are necessary to ensure the successful transformation of the land registration system in Indonesia